Museum Sri Baduga dalam Paradigma New Museology - Fitriany, Detty (PANTUN: Jurnal Ilmiah Seni Budaya, 2016)
Museum experiences a paradigm shift from the traditional museum into a modern museum then post-modern museum which gave birth to the movement of the eco-museum. As a museum established in the modern era, Museum Sri Baduga needs to adjust to the new paradigm of museology. The focus of this study is to find the suitability of the museum Sri Baduga current principles with the principles of eco-museum both physical and managerial aspects of the museum and what changes should be madeto achieve the ideal eco-museum. Methods of data collection is done with literature study and field observation. Methods of data analysis is conducted qualitatively by using the Eco-museum guidance indicator of Corsane Gerard (2006. The presentation method of data analysis is done informally in the form of a narrative. The findings in this study are the strengths and opportunities that are owned by the museum Sri Baduga to meet the principles of eco-museum that cannot be completed at this time. Keywords: new museology, Museum Sri Baduga, eco-museum